Comparative Analysis of Indonesia's Land and Sea Border Vulnerabilities: Immigration Law Enforcement Study in 2024 - Tison Horison Haloho; Stanislaus Riyanta (Green Publisher Indonesia, 2025)
violations by foreign nationals, especially in land and sea border areas, poses a threat that is both administrative and criminal in nature. This study aims to identify patterns of immigration violations based on the nationality of the perpetrator, the location of the violation, and the articles of law violated at the land and sea borders, as well as to examine the implications for the national legal system. The method used is comparative analysis based on secondary data of violation cases in 2024. The results show 714 cases, with a dominance of serious violations such as abuse of residence permits and falsification of documents. The countries of origin of most violators are China, the Philippines, Malaysia, and Papua New Guinea. Law enforcement carried out against violators reflects the practice of crimmigration, namely the convergence of criminal and immigration law. These findings emphasize the importance of strengthening immigration control at the border as part of efforts to build national resilience in facing the threat of illegal migration and transnational crime.